Factors Influencing Intraoperative Rupture of Intracranial Aneurysms - Khadka, Namrata; Rajbhandari, Binod; Aryal, Sameer; Bhattarai, Sushil Mohan; Shrestha, Rajendra; Jha, Rajiv (Journal of Institute of Medicine Nepal, 2024)
Introduction Intraoperative rupture (IOR) is the most anticipated yet dreaded complication during intracranial aneurysmal surgery, leading to severe adverse outcomes. This study aims to analyze various risk factors contributing to IOR. Methods It was an analytical study of 46 cases of intracranial aneurysms treated at Department of Neurosurgery, Bir Hospital including both ruptured (n=43) and unruptured (n=3) aneurysms. Incidence of IOR, demographic data, preoperative grading scales, aneurysm morphology, phases and severity of IOR along with postoperative complications and outcomes were assessed. Results IOR occurred in 28.26% (13/46) cases of intracranial aneurysms. Most common aneurysm was anterior communicating artery aneurysm (43.5%, 20/46) with majority of IOR (65.1%).Younger patients and males had higher rates of IOR, and early surgical intervention (within 72 hours) was associated with increased incidence (69.2%,9/13). Although preoperative factors showed no direct correlation with IOR, aneurysm size and morphology-dome width and height ratio (W/H) and irregular shapes of aneurysm emerged as critical risk factors (p<0.05). Temporary clipping during surgery appeared to reduce IOR, mostly mild (13.04%, 6/13) and occurred in second phase (17.39%; 8/13, during microdissection and neck preparation). However, IOR did not have adverse effects on postoperative complications and Glasgow Outcome Scale Extended (GOSE) at discharge. Conclusion Incidence of IOR was 28.65%. Younger age, males, higher Fisher score, early timing of surgery of aneurysms and larger size increased the risk, while use of temporary clip reduced the risk. Dome H/W ratio and irregular shapes of aneurysm were important factors predicting IOR in this study.